DIFFERENCES OF SITUATIONAL AND MOTOR ABILITIES IN DEFENSE AT THE WORLD JUNIOR HANDBALL CHAMPIONSHIP - Sanja Bajgorić; Muris Đug (Sport Scientific And Practical Aspects, 2025)
The research was conducted in order to determine the differences in situational-motor abilities in the defense of men’s junior national teams at the 2013 World Handball Championship. Situational - motor abilities in the defense of the national team of Bosnia and Herzegovina in relation to the national teams of Croatia, France, Sweden and Spain were analyzed. The following variables were used to determine differences in defense: SKODEKUK / PR - total - average number of jumps in defense of the whole team, SKODUK / PR1 - total - average number of jumps in defense first player of defense, SKODUK / PR2 - total - average number of jumps in defense second defensive player, SKODUK / PR3 - total - average number of defensive jumps third defensive player, SKODUK / PR4 - total - average number of defensive jumps fourth defensive player, SKODUK / PR5 - total - average number of defensive jumps fifth defensive player and SKODUK / PR6 - total – average number of jumps in the sixth defense player. To determine the partial quantitative differences of variables, which measure the total and average number of attempts to perform an element in the area of situational - motor abilities in defense, we used the mean difference of mean (hereinafter MD), which calculated the average values of selected variables. The average values of variables for the assessment of situational - motor abilities in defense were also calculated. The variable SKODUK / PR4 - total - average number of jumps in the defense of the fourth player shows a statistically significant negative difference in the jumps in the defense of the fourth player between the fourth player in the defense of Bosnia and Herzegovina and the fourth player in the defense of Croatia and Sweden. In the variable SKODUK / PR6 - total - average number of jumps in the defense of the sixth defense player, a statistically significant negative difference can be seen between the sixth player in the defense of the national team of Bosnia and Herzegovina and the sixth player in the defense of Sweden.